2018
DOI: 10.1074/jbc.ra117.001322
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-conjugating enzyme E2 D1 (Ube2D1) mediates lysine-independent ubiquitination of the E3 ubiquitin ligase March-I

Abstract: March

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…The five most central members of the Cluster 1 network (based on betweenness centrality) were SQSTM1 , UBE2D1 , CBL , TRIM21 , and HIF1A ( Supplementary Table 3 ). SQSTM1 is involved in multiple protein degradation pathways, UBE2D1 is a ubiquitin-conjugating enzyme, and CBL and TRIM21 are both ubiquitin ligases – although all four are likely to play an important role in the response to ROS, and SQSTM1 is a well-characterized NRF2 target gene, the network centrality of these proteins can be explained by the broad protein-protein interaction spectrum associated with ubiquitin mediated degradation [41] , [42] , [43] , [44] . However, HIF1A , which encodes HIF1α, is typically associated with hypoxic stress and, therefore, an unanticipated member of this gene set.…”
Section: Resultsmentioning
confidence: 99%
“…The five most central members of the Cluster 1 network (based on betweenness centrality) were SQSTM1 , UBE2D1 , CBL , TRIM21 , and HIF1A ( Supplementary Table 3 ). SQSTM1 is involved in multiple protein degradation pathways, UBE2D1 is a ubiquitin-conjugating enzyme, and CBL and TRIM21 are both ubiquitin ligases – although all four are likely to play an important role in the response to ROS, and SQSTM1 is a well-characterized NRF2 target gene, the network centrality of these proteins can be explained by the broad protein-protein interaction spectrum associated with ubiquitin mediated degradation [41] , [42] , [43] , [44] . However, HIF1A , which encodes HIF1α, is typically associated with hypoxic stress and, therefore, an unanticipated member of this gene set.…”
Section: Resultsmentioning
confidence: 99%
“…shRNA knockdown of the E2 Ube2D1 strongly stabilized wild-type MARCH1; however, whether this also applies to lysine-free MARCH1 was not addressed. While the responsible E3 ligase(s) has not yet been identified, it appears that MARCH1 itself is not responsible, or is at least not required, as mutation of catalytic residues to disable its E3 activity did not prevent its ubiquitination [46].…”
Section: Non-lysine Ubiquitination Targets a Variety Of Cellular Procmentioning
confidence: 99%
“…For examples, MARCH1 keeps a low protein level in antigen presentation cells (APCs) of human and mice by its TM-mediated dimerization, leading to autoubiquitination and degradation (57). However, it has been demonstrated that both wild-type and catalytically inactive MARCH1 are ubiquitinated in HeLa cells, suggesting that MARCH1 can be ubiquitinated by as yet unidentified E3 ligases (58). The stability of MARCH5-8, and 10 is tightly regulated by their RING-CH finger-mediated atutoubiquitination (4, 12, 15, 18, 27, 29).…”
Section: Properties Of the March E3 Ligase Family Membersmentioning
confidence: 99%